ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN PESAWAT TELEPON PADA PT. DAMAI SEJATI MAKASSAR - Sultan Iskandar (AkMen JURNAL ILMIAH, 2014)
This study aims to identify and analyze the application of accounting information systems, in particular the implementation of systems and procedures implemented by the sale of PT. True peace Makassar. The analytical method used is descriptive comparative ie an analysis that describes and compares the application of accounting information systems sales , particularly in the application of systems and procedures implemented by the company sales with sales accounting information systems, in particular the implementation of systems and procedures for effective sales based on review of literature through the literature on systems and procedures sale". The results of this study show that Overall , sales of systems and procedures implemented by the management of PT. True peace Makassar has been implemented effectively and fairly. Systems and procedures applied in the company is one of the means of support required by the management company to be able to obtain assurance that all members or any elements within the company has been able to work well together to achieve corporate objectives .